KEPENTINGAN CINA DAN RUSIA DALAM TREATY OF GOOD-NEIGHBORLINESS AND FRIENDLY COOPERATION BETWEEN THE PEOPLE'S REPUBLIC OF CHINA AND THE RUSSIAN FEDERATION TAHUN 2001 - Maha Patma, Anak Agung Bagus Arya Wipra; Fasisaka, Idin; Suwecawangsa, Adi P (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research aims to explain China and Russia’s interest in the Treaty of Good-Neighborliness and Friendly Cooperation Between the People's Republic of China and the Russian Federation in 2001. The treaty between China and Russia in 2001 is conducted because both China and Russia have their own interests in that treaty, and all of those interests will be discussed in depth in this research. The data in this research was analysed by using the concept of peaceful coexistence and strategic partnership. This research perceives that the treaty made between China and Russia was carried out with the aim of achieving interests of both nation while still prioritising the use of peaceful coexistence and strategic partnership as a concept. Key Words: Peaceful Coexistence, Strategic Partnership.